HUBUNGAN TRADISI MASYARAKAT DENGAN KEJADIAN BBLR DI UPT PUSKESMAS LAMURUKUNG - Arfan Nur (LPPM Institut Sains dan Kesehatan Bone, 2021)
Abstract. Background: Problems with babies with LBW are still a major cause of pernatal morbidity and mortality, and have a serious impact on the quality of future generations, which will hinder children's growth and mental development, as well as affect the decline in intelligence.Objective: To determine the relationship of the incidence of newborns with low birth weight related to community traditions at the Lamurukung Puskesmas UPT.Method: This research uses descriptive method which aims to present a complete picture of the incidence rate of newborns with low birth weight by describing a number of variables. So determined the number of samples that meet the criteria as many as 30 people.Results: The results showed that there is a relationship between Community Traditions and Low Birth Weight Babies, the results of the chi square test obtained p-value = 0.000 p <0.05.Conclusion: There is a relationship between education, knowledge and community traditions / culture with the incidence of low birth weight babies.